2022
DOI: 10.29140/jaltcall.v18n2.519
|View full text |Cite
|
Sign up to set email alerts
|

Student engagement with computermediated teacher written corrective feedback: A case study

Abstract: Much of the research on the effectiveness of written corrective feedback (WCF) scope and strategies has been (quasi-)experimental, generating results peripherally related to authentic classroom contexts. Underpinned by a multidimensional conceptual framework of student engagement with WCF, this classroombased study has explored the scope and strategies used by the teacher regarding WCF. It also investigated how two ESL university students behaviorally, cognitively, and affectively engaged with the scope and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 44 publications
0
16
1
Order By: Relevance
“…These findings are in line with AbuSeileek and Abu Sa'aleek (2012) and (Safitri, 2021) who found that lecturers use track changes and word processors when providing CF. The results, however, refute the claim made by Henderson and Phillips (2014) that users can now record their computer screens and add voiceovers using screen capture software to provide remedial feedback and Koltovskaia and Mahapatra (2022) who found that the most frequently used feedback mode was the directly written CF.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…These findings are in line with AbuSeileek and Abu Sa'aleek (2012) and (Safitri, 2021) who found that lecturers use track changes and word processors when providing CF. The results, however, refute the claim made by Henderson and Phillips (2014) that users can now record their computer screens and add voiceovers using screen capture software to provide remedial feedback and Koltovskaia and Mahapatra (2022) who found that the most frequently used feedback mode was the directly written CF.…”
Section: Discussioncontrasting
confidence: 54%
“…AbuSeileek and AbuSeileek (2012) assert that the computer acts as a teaching and learning tool and can be used in assessing students' write-ups while providing necessary feedback. It can also be referred to as the textual input delivered by computer software that has been installed in order to directly or indirectly repair students' writing faults (Koltovskaia and Mahapatra, 2022). It is a relatively new research path and has affective impacts on students in tertiary institutions (Al-Ansi et al ., 2019; Bahari, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, CF has also been perceived as ineffective and even potentially "harmful … [to] students' ability to write accurately" (Truscott, 2007, p. 270) and to use the language correctly in practical ways in communication as it may impede learners' fluency, overemphasize form at the expense of meaning, and overlook underlying causes of errors (Truscott, 2007(Truscott, , 2016. In addition, a study conducted by Koltovskaia and Mahapatra (2022), which examined two ESL students' behavior, cognitive, and affective engagement with computer-mediated teacher CF, highlights that while direct CF "provides a solution for students," they "do not have to use a lot of cognitive resources to resolve the issue" (p. 306). In this way, it may not guarantee learning.…”
Section: Corrective Feedback In Efl Writingmentioning
confidence: 99%